(untitled) (ex æquo, 2013)
How can we recognize a feminist-queer happening? It is hard to answer simply and briefly to this question. Taking the «Joan of Arc case» as example, a happening which took place early 2010 in Lille (France), it seems that some features evidences do not lie, especially the use of the pink. However, everyone does not share the meaning of this color, on the contrary, the use of the pink generates questions and discordant interpretations. All this indicates patently conflicts and divergences within the LGBT movements in France.